Hearing [Hören] is Defenseless—without Listening [Hören]: On Possibilities and Difficulties - Lachenmann, Helmut (Circuit, 2003)
Composer Helmut Lachenmann published this seminal essay in 1985 in Germany, and it has since served as the basis point for a sustained reflection on the conditions of listening. It has also had a certain impact on the orientation of musicological research, particularly in Germany and France. Translated for the first time into English, Lachenmann begins by analyzing the place of modern music in society, in order to expand on a theory of listening which broaches phenomenological terrain: composing becomes the creation of new listening situations rather than the construction of a musical language in abstracto. Through a study of works of the standard repertoire (Beethoven) as well as through twentieth-century offerings (Webern and Lachenmann himself), he gives concrete examples of what a listening which is not "lulled to sleep by the common rituals" might be.